INTERNATIONAL LEGAL COOPERATION AND THE PRINCIPLE OF JURISDICTION: LESSONS FROM FAMILY LAW - DOI 10.5935/2448-0517.20200030 - Gama, Guilherme Calmon Nogueira da (Juris Poiesis - Qualis A3, 2020)
This extended abstract aims to point out the need to conceptualize the principle of jurisdiction and to identify its main controversies in the field of international legal cooperation. Issues related to the notion of public order, private autonomy, rights and procedural guarantees, among others, have proved to be fundamental for a more adequate understanding of the subject of jurisdiction from the perspective of international legal cooperation. The specific study will address Hague ConventionÂ´s approach to the civil aspects of international child abduction related to the theme "right of custody" under the Family Law.